The Relationship Between Self-Efficacy and Peer Association with Mathematics Learning Outcomes of Grade X Students of SMAN 4 Palangka Raya - Haryani, Desti; ., Pancarita; Hasanah, Rindan (JURNAL PENDIDIKAN, 2024)
This study aims to find out: (1) The relationship between self-efficacy and mathematics learning outcomes of grade X students of SMAN 4 Palangka Raya, (2) The relationship of peer association with mathematics learning outcomes of grade X students of SMAN 4 Palangka Raya, (3) The relationship of self-efficacy and peer association with the mathematics learning outcomes of grade X students of SMAN 4 Palangka Raya. This research was carried out in the even semester of the 2023/2024 academic year. The study population was 515 students with a sample of 221 students. Based on the results of the trial, the self-efficacy questionnaire obtained 36 valid statements with , the peer association questionnaire obtained 28 valid statements with , and the mathematics learning outcomes test obtained 21 valid questions with . Based on the results of the prerequisite analysis test, namely the normality test, obtained for self-efficacy data , peer association data , and mathematics learning outcome test data , while the value , because the three data are not normally distributed, so the test used is nonparametric statistical analysis, namely Spearman rank correlation. The results of this study can be concluded: (1) There is a positive relationship between self-efficacy and mathematics learning outcomes of grade X students of SMAN 4 Palangka Raya; (2) There is a positive relationship between peer association and mathematics learning outcomes of grade X students of SMAN 4 Palangka Raya; (3) There is a positive relationship between self-efficacy and peer association with mathematics learning outcomes of grade X students of SMAN 4 Palangka Raya